2010
DOI: 10.1590/s1807-59322010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic, Morphometric and Autonomic Patterns in Hypertensive Rats - Renin-Angiotensin System Modulation

Abstract: BACKGROUND:Spontaneously hypertensive rats develop left ventricular hypertrophy, increased blood pressure and blood pressure variability, which are important determinants of heart damage, like the activation of renin-angiotensin system.AIMS:To investigate the effects of the time-course of hypertension over 1) hemodynamic and autonomic patterns (blood pressure; blood pressure variability; heart rate); 2) left ventricular hypertrophy; and 3) local and systemic Renin-angiotensin system of the spontaneously hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
(37 reference statements)
2
21
0
3
Order By: Relevance
“…An increase of 480/350 (systolic and diastolic) BP has been shown in bodybuilders while performing leg press exercise (6,7). Concentric cardiac hypertrophy might also result from pressure overload observed in many pathologic conditions, such as hypertension (8). However, this type of hypertrophy is followed by diastolic and/or systolic dysfunction and a disproportionate increase in the thickness of the left ventricle posterior wall and interventricular septum (8)(9)(10).…”
Section: Concentric Cardiac Hypertrophy Induced By Resistance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of 480/350 (systolic and diastolic) BP has been shown in bodybuilders while performing leg press exercise (6,7). Concentric cardiac hypertrophy might also result from pressure overload observed in many pathologic conditions, such as hypertension (8). However, this type of hypertrophy is followed by diastolic and/or systolic dysfunction and a disproportionate increase in the thickness of the left ventricle posterior wall and interventricular septum (8)(9)(10).…”
Section: Concentric Cardiac Hypertrophy Induced By Resistance Trainingmentioning
confidence: 99%
“…Concentric cardiac hypertrophy might also result from pressure overload observed in many pathologic conditions, such as hypertension (8). However, this type of hypertrophy is followed by diastolic and/or systolic dysfunction and a disproportionate increase in the thickness of the left ventricle posterior wall and interventricular septum (8)(9)(10). Sometimes, the physiological hypertrophy developed by high level strength athletes presents a macroscopic structure similar to pathological hypertrophy, which could be incorrectly interpreted as pathological.…”
Section: Concentric Cardiac Hypertrophy Induced By Resistance Trainingmentioning
confidence: 99%
“…In vivo studies have shown that the SHR has an increased cardiac output (CO) with normal total peripheral resistance (TPR) in the early stages of HTN, but as the animal progresses into the established HTN state, the CO returns to normal while the hypertrophied blood vessels produce an increase in the TPR (Smith & Hutchins, 1979). The SHR also develops left ventricular hypertrophy (LVH), increased BP and BP variability; all of which are important indices of heart damage (Zamo et al, 2010). An advantage of the SHR is that compounds which lower BP in this strain also lower BP in hypertensive humans.…”
Section: The Spontaneously Hypertensive Ratmentioning
confidence: 99%
“…The RAABS/RAAS is a key physiologic regulator of vascular tone, salt and water balance, BP, bradykinin system and pituitary gland hormones (Gradman, 2009;Lacolley et al, 2009;Zamo et al, 2010). Short term activation of the system is geared towards maintaining intravascular volume, BP, and tissue repair; however, chronic activation leads to chronic vasoconstriction and elevation of BP, VSMC growth/migration, endothelial dysfunction, oxidative stress, the release of cytokines and inflammatory cell activation, fibrosis, and thrombosis.…”
Section: System (Raabs)mentioning
confidence: 99%
“…Previously, we investigated the RAS modulation during the timecourse of hypertension, and the effects on hemodynamic and morphometric parameters (Zamo et al 2010). This work was undertaken to investigate the effects of swimming training (ST) in different stages of hypertension on 1) hemodynamic patterns (blood pressure and heart rate); 2) left ventricular hypertrophy and collagen volume fraction; and 3) local and systemic RAS of spontaneously hypertensive rat (SHR).…”
Section: Introductionmentioning
confidence: 99%